Employee risk recognition and reporting of malicious elicitations: longitudinal improvement with new skills-based training - Deanna D. Caputo; Lura Danley; Nathaniel J. Ratcliff (Frontiers in Psychology, 2024)
Numerous security domains would benefit from improved employee risk recognition and reporting through effective security training. This study assesses the effectiveness of a new skills-based training approach to improve risk recognition and reporting of malicious elicitations. Malicious elicitations are techniques that strategically use conversation (i.e., online, in writing, in person, or over the phone) with the sole purpose of collecting sensitive, non-publicly available information about business operations, people, or technological assets without raising suspicion. To an untrained observer, a skilled elicitor can make conversations seem analogous to many professional networking situations such as those experienced over email and at conferences. A 12-month longitudinal experimental study was conducted to test training effectiveness on employees of a large corporation that focuses on serving national security needs and the public interest. Half of participants were randomly assigned to receive traditional awareness-based training (i.e., reviewing informational slides) while the other half of participants received a new skills-based training that allowed them—over the course of five weeks—to iteratively practice skills learned in the training and receive feedback on their performance in their day-to-day work environment. Following training for both experimental groups, malicious elicitations and benign professional networking test messages were sent (via email & text message) to unaware employee participants for 12 months. Findings revealed that skills-based training improved reporting of malicious elicitations and lasted for up to 12 months compared to traditional awareness-based training.